On the search for mimetic patterns in environmental disclosure: an international perspective. Issue 7 (3rd October 2018) - Cormier, D.; Gomez-Gutierrez, L.
ABSTRACT: In this paper, we assert and test the proposition that environmental disclosure (ED) is structured by institutionalised myths and that is why ED is decoupled from environmental performance and media pressures. Focusing on firms from Canada, France and Germany, findings show that ED mimetic isomorphism for different topics varies among countries and by industry sensitiveness to the environment. The results corroborate the institutional presumption that institutionalised myths vary among different contexts. Our findings also suggest that institutionalised ED structures may not reflect environmental performance, mimetic patterns being affected by environmental performance. However, the decoupling between ED mimetic isomorphism and environmental performance decrease when firms' ED credibility is questioned by the media.